Determining the topology of peroxisomal proteins using protease protection assays - Francisco, T (2017)
Protease protection assays are powerful tools to determine the topology of organelle proteins. Their simplicity, together with the fact that they are particularly suited to characterize endogenous proteins, are their major advantages and the reason why these assays have been in use for so many years. Here, we provide a detailed protocol to use with mammalian peroxisomes. Suggestions on how these assays can be controlled, and how to identify some technical pitfalls, are also presented.